G280(P) Improving timely detection and management of septic paediatric patients presenting to the emergency department. (24th May 2017) - Tomlinson, N; Burridge, R; Pratley, S
Abstract : Background: It has been widely reported that reducing the time to diagnosis of severe sepsis is a critical component of reducing mortality from sepsis-related multiple organ dysfunction. There has therefore been increasing pressure for front line staff in emergency departments to ensure rapid detection and management of children presenting with suspected sepsis in order to improve outcome. Aims: To design and implement a sepsis screening sticker for use in triage and a complimentary sepsis proforma for use in high risk patients, drawing on both The Sepsis Trust and NICE guidelines. The aim is for all appropriate patients to have these tools completed. Methods: Retrospective audit from October 2015 to April 2016 in a children's emergency department in a general district hospital. Three audit cycles of 100 patients each, assessing use of a sepsis triage sticker and sepsis proforma and using results to shape alterations to these tools after each audit cycle. Results: Correct use of the triage stickers improved from 68% to 76%, with a sepsis proforma being started in an increasing number of patients who triggered on the triage stickers between October 2015 and April 2016 (45% and 80% respectively). Surprisingly few patients triggered two or more criteria on the triage sticker (5%–11%), despite wide held belief that this would be higher given that temperature and heart rate are two of the criteria. During the January 2016 audit cycle one patient who did have red flag sepsis received antibiotics for sepsis in less than an hour. Conclusion: Despite initial reservations, we found that the sepsis tools discriminated well. By implementing a strategy to streamline the triage process and draw attention to important assessment criteria, it is possible to facilitate early detection of children who may potentially be septic and require urgent medical attention. We are continuing to audit these tools, the results of which will be used in conjunction with the new 2016 NICE guidelines to raise awareness among front line staff and reduce morbidity and mortality from sepsis among the paediatric population.